Utilization of Angsana Leaves (Pterocarpus indicus Willd) as a Natural Coagulant for Palm Oil Mill Effluent (POME) Treatment - Elvitriana; Nasir, Muhammad; Nizar, Muhammad; Viena, Vera; Makmur, Teuku; Suhendrayatna (Postgraduate, University of Mataram, 2023)
This research aims to prepare natural coagulants from Angsana leaves (Pterocarpus indicus willd) for Palm Oil Mill Effluent (POME) treatment, especially reducing main variables such as TSS, COD, and pH. The amounts of 100 mesh Angsana powder (5, 10, 15, and 20 grams) were extracted using NaCl solvent with concentrations of 0.25 M and 0.5 M, respectively. The extract (200 mL) were added to 500 mL of POME and stirred (180 rpm) for 30 minutes. The concentrations of TSS, COD, and pH in POME were analyzed. Results showed that the coagulation-flocculation process using Angsana leaves powder was able to reduce COD by 55.79% at a coagulant dose of 5 g/L with 0.25 M NaCl solvent and TSS by 99.75% at a dose of 20 g/L with 0.25 M NaCl solvent. However, treatment using Angsana leaves extract was not able to reduce COD to the predetermined quality standard limits while the TSS value met the quality standard. Therefore, POME treatment still requires further processing.